AN ANALYSIS OF TEACHER’S LESSON PLAN FOR LEARNING ENGLISH THROUGH GOOGLE CLASSROOM IN JUNIOR HIGH SCHOOL - Fitriani, Ni Wayan; Budiarta, Luh Gd Rahayu (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Online learning is something new for teachers and students, so there are various obstacles to it. This study aims to: analyze the preparation of EFL teachers in preparing lesson plans and identify and describe teacher difficulties in preparing lesson plans for EFL students. This study uses a qualitative descriptive research design. Data on teacher preparation and difficulties faced by teachers in preparing lesson plans were taken using a questionnaire by determining five aspects, namely: 1) learning objectives, 2) learning materials, 3) learning activities, 4) media and learning resources and, 5) learning assessment. The study results are that the teacher fulfills all the steps in compiling a one-page lesson plan, which fulfills the steps provided by the instrument. Regarding the problems faced in the process of preparing lesson plans by teachers, it can be synthesized that there are six difficulties encountered by teachers, such as 1) stating learning objectives that contain behavior (B), 2) connecting learning objectives to core competencies, 3) compiling learning materials based on indicators. Learning, 4) selection of learning media based on learning objectives, 5) selection of learning media based on learning materials, and 6) selection of assessment based on learning objectives.